The effect of inhalation aromatherapy with damask rose essence on pain intensity and anxiety in burned patients: A single-blind randomized clinical trial. Issue 8 (December 2020) - Sadeghi, Narges; Azizi, Azim; Asgari, Shadi; Mohammadi, Younes
Highlights: Pain and anxiety are one of the major problems of burn patients. Despite the use of different medications, patients still suffer from these two problems. In this study evaluated the short-term and long-term effects of Aromatherapy with Damask rose essence on pain in burn patients. Inhaled aromatherapy with Damask rose essence can reduce the pain intensity and state anxiety in burn patients. Therefore, it is recommended to use Damask rose essence, as an easy and affordable method along with other treatments. Abstract: Introduction: Pain and anxiety are a major problem of burn patients. Despite the use of different medications, patients still suffer from these two problems. Aromatherapy along with medication may help in alleviating these symptoms. This study aimed to investigate the effect of inhalation aromatherapy with damask rose essence on pain and anxiety in burn patients. Methods: This three group clinical trial was conducted on 120 patients with burns less than 30% TBSA. The patients were randomly allocated into three groups, aromatherapy damask rose essence, placebo, and control. The pain intensity was assessed using visual analogue scale prior to intervention, immediately before, and 15 min after dressing. Anxiety was measured using Spielberger Inventory at before intervention and 15 min after dressing, also the prolonged effect of intervention on pain was assessed by number of the analgesics drugs received for four hours after dressing change. The intervention included inhalation of 6 drops of 40% damask rose essential oil in the damask group, and six drops of distilled water in placebo group one hour before dressing change. The control group received no intervention. Results: Baseline state–trait anxiety and pain intensity were similar in these three groups (p > 0.05). We found a significant reduction in pain intensity immediately before and after dressing and state anxiety after dressing in the damask group compared to the placebo and control groups (p < 0.001). However, we found no significant difference between the placebo and control groups in terms of these variables at these times (p > 0.05). Also, we found no significant difference among three groups in frequency of analgesics drugs and trait anxiety after intervention (p > 0.05). Conclusion: Inhaled aromatherapy with Damask rose essence reduces subjective pain intensity and state anxiety in burned patients. Therefore, it is recommended considering use of damask rose essence, as an easy and affordable method along with other treatments.